THE SOCIAL AND ECONOMIC ASPECTS OF NGOS OFFERING PSYCHOSOCIAL SERVICES IN LITHUANIA - Leonavičius, Vylius (Sociologija. Mintis ir veiksmas, 2015)
In Lithuania the NGO sector is currently undergoing dramatic changes, alongside the public and private sectors. Its complexity is apparent not only in its relative growth and intrinsic significance, but also in its possibilities for integration into the other sectors. This complexity produces difficulties in understanding and defining third-sector organisations. This article addresses the issue of the compatibility of the social and economic aspects of Lithuanian NGOs with sustainable development. The relation between NGOs and the market is not clearly defined; for instance, it is often said that voluntary NGOs cannot compete with the service sector in terms of incomes. Such notions make an understanding of the role and place of NGOs between public and private sectors even more remote. Qualitative research shows that the concept of the NGO is unclear not only to the public but also to government and business. If the participation of NGOs in the market is becoming problematic, it is because their origin, nature and activities are very complex. Over half of all NGO founders already knew, at the time of inception, that the social programmes or missions of the organisations they had created would involve economic activity. While NGO leaders declare that such activity is necessary for survival, a necessary supplement to the main work of their organisations, informants agree that the sale of services should never become the main impetus of NGOs, since this would risk their ability to question existing social structures, to pose solutions to pressing social problems, and to enter into partnerships with society, the market and the state.
Keywords: NGO; market and NGO; sustainability